Implementasi Kurikulum Merdeka di TK Witri 1 kota Bengkulu - Imelia Utami, Femi; Sahani, Freti; Oktaviani, Regina; Bahri, Husnul (UIN Fatmawati Sukarno Bengkulu, 2025)
This is a problem that is often felt by schools, including early childhood teachers, at every curriculum change. There are three alternative choices in its implementation. To provide an understanding of the nature and how to develop an independent curriculum, it is important to conduct this research. This type of research is qualitative research. The research location is defined as the place where the research was conducted. This research was conducted at Witri 1 Kindergarten, Bengkulu City. The research instruments used were interviews, observations and documentation studies. The results showed that the independent curriculum goes hand in hand with the concept of independent learning launched by the Minister of Education and Culture. In compiling an independent curriculum that needs to be considered is the basic framework and curriculum structure. The result of this study is that the independent curriculum goes hand in hand with the concept of independent learning launched by the Minister of Education and Culture. In compiling an independent curriculum, it is necessary to pay attention to the basic framework and structure of the curriculum.